Annulment of the Marriage Contract Due to a Change in One Spouse’s Religion: A Comparative Study - Salman Rajab, Researcher. Hussam El-Din; Prof.Dr. Ali Abdul Ali Al-Asadi , Prof.Dr. Ali Abdul Ali Al-Asadi; Abdel Samad Al Shawi, Prof. Dr. Abdel Basset (Basra studies journal, 2025)
Islam places great importance on the continuity of the marital bond between spouses unless a legitimate impediment arises to prevent it. One of the conditions for the validity of the marriage contract is that the woman must not be in a state of ihram, whether temporary or permanent, which may render the marriage contract subject to annulment in the event of a change in the religion of either spouse. Islamic law addresses such cases by either allowing the marriage to continue or by dissolving it. Personal status laws in Arab countries regulate the application of Sharia in cases involving a change in the religion of one of the spouses, as this matter is regarded as a right of God. This study reviews the impact of religious conversion on the marriage contract from the perspectives of Muslim jurists, including the Imami, Hanafi, Shafi’i, Maliki, and Hanbali schools. It also compares the positions of personal status laws in Iraq, Yemen, Kuwait, and Jordan regarding the annulment of the marriage contract due to a change in religion. Special attention is given to Iraq’s Personal Status Law No. 188 of 1959, Yemen’s Law No. 20 of 1998, Kuwait’s Law No. 51 of 1984, and Jordan’s Law No. 36 of 2010, as they contain specific provisions related to this issue.